PENGEMBANGAN MODUL FISIKA STATISTIK BERBASIS LEARNING CYCLE TERINTGRASI PROFETIK - Emawati, Imas Ratna; Sugianto, Sugianto; Hartini, Tri Isti; Hardiyanto, Mohammad; Diningsih, Berliani Amanda; Syaadah, Syiffa Nurul; Widyanti, Sekar Tyas; Fahira, Adinda Permata (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Development is research with the output of a product, either simply or structurally. Development research is used to design and produce a product systematically and meet internal practicality criteria. universal and use the framework of science. To realize physics education students, of course, the statistical physics module is in accordance with student needs. This study aims to develop a learning cycle-based statistical physics module/book. The method used is Research and Development (R&D) with the 4-D model (Four D) which is a learning device development model. The 4D development model consists of 4 main stages, namely: 1. Define (Delimitation), 2. Design (Design), 3. Develop (Development) and 4. Disseminate (Dissemination), adapted to the 4-P Model, namely Defining, Designing, Development , and Dissemination. The products developed are in the form of modules or textbooks. The data source is physics education students at FKIP UHAMKA. Data sources were obtained from informants, documents, activity processes and validators. Data collection techniques using questionnaires and documentation, while the data analysis techniques used the gain score test, quantitative and qualitative descriptive analysis. Model validation was carried out using expert judgment using the Delphi technique.The results of this study are the modules / textbooks of physics statistics. Validation from material experts / academic experts, display media and revisions were 77.03 and 86.38 with very good categories. The results of the reaction evaluation to measure the respondents' responses to the quality of the implementation of the modules / textbooks were considered good. In the effectiveness of the use of modules/textbooks there are significant changes to students before and after, as evidenced by the high effectiveness or feasibility of the statistical physics module/textbook in the criteria of